Original paperChanges in blood eosinophilia during omalizumab therapy as a predictor of asthma exacerbation - Skiepko, Roman; Ziętkowski, Ziemowit; Łukaszyk, Mateusz; Budny, Wojciech; Skiepko, Urszula; Milewski, Robert; Bodzenta-Łukaszyk, Anna (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2014)
Introduction : Omalizumab is a monoclonal anti-immunoglobulin E antibody developed for the treatment of severe allergic asthma. The number of exacerbations used as a parameter of omalizumab therapy efficacy may be insufficient in many cases due to a relatively short time to first evaluation (16 weeks). Therefore, it is advisable to look for parameters of more prognostic value while continuing omalizumab therapy. Aim : To evaluate usefulness of analysis of changes of blood eosinophilia after 16 weeks of omalizumab therapy as a predictor of asthma exacerbations. Material and methods : The study was conducted on a group of 13 patients with severe persistent allergic asthma treated with omalizumab. Blood eosinophil counts were measured before and after 16 weeks of anti-IgE therapy. On the basis of percentage of eosinophilia decrease (> 50% or < 50% of the initial value), patients were divided into two groups. Analysis of the asthma exacerbation rate during 12 months and time to first exacerbation was performed. Results : In the group with a high decrease in blood eosinophil counts (group 1) we showed a statistically significantly lower asthma exacerbation rate in 12 months compared with the group with a low decrease in blood eosinophil counts (group 2) ( p = 0.02). We also observed the tendency to longer time to first asthma exacerbation in group 1 compared to group 2 ( p = 0.06). Conclusions : Our results showed that a decrease in blood eosinophilia during omalizumab therapy can be a predictor of asthma exacerbation. Evaluation of changes in blood eosinophil count should be taken into the consideration while estimating response to anti-IgE therapy in patients with severe allergic asthma.